Development of flexible conductive membrane. (2022) - Yadav, Sudiksha; Panwar, Varij; Umer Ansari, Mohd
Abstract: Electrically Conductive Polymers is having immense scope under flexible electronics they are having huge advantages in wearables electronics and smart gadgets. In our research, we determines the conductive, dielectric and piezoelectric properties of Poly Vinyl Alcohol (PVA) and Poly Styrene Sulfonic Acid (PSSA) at frequency band of 20 Hz–10 MHz. Firstly the Dielectric constant of pure PVA membrane is least, though it is increased by adding PSSA. We use Impedance Analyzer to measure various properties as mentioned earlier. In our research we concluded that on adding 0.4 gm of PSSA to PVA we find the best results.